2020
DOI: 10.1097/md.0000000000019597
|View full text |Cite
|
Sign up to set email alerts
|

Nucleobindin 2 expression is an independent prognostic factor for bladder cancer

Abstract: Nucleobindin 2 (NUCB2) has been reported to play an important role in both tumorigenesis and cancer progression. This study aimed to examine the clinical significance of NUCB2 expression urothelial carcinoma of the bladder (UCB). The expression level of NUCB2 and its correlation with clinicopathological parameters was analyzed in 225 UCB tissues by immunohistochemistry. Kaplan–Meier analysis and Cox proportional hazards regression models were used to investigate the correlation between NUCB2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The first study on nucleobidin-2/nesfatin-1 function in cancer was made in 2012 in breast cancer patients [ 41 ]. Since then, there have been single reports on NUCB2/NESF-1 in the most common human cancers, i.e., breast, colon, gastric, bladder, ovarian, endometrial, prostate, papillary thyroid cancers, renal cell carcinoma, and glioblastoma ( Table 1 ) [ 41 , 46 , 47 , 48 , 53 ]. In general, the expression of NUCB2/NESF-1 is associated with cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first study on nucleobidin-2/nesfatin-1 function in cancer was made in 2012 in breast cancer patients [ 41 ]. Since then, there have been single reports on NUCB2/NESF-1 in the most common human cancers, i.e., breast, colon, gastric, bladder, ovarian, endometrial, prostate, papillary thyroid cancers, renal cell carcinoma, and glioblastoma ( Table 1 ) [ 41 , 46 , 47 , 48 , 53 ]. In general, the expression of NUCB2/NESF-1 is associated with cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the expression of NUCB2/NESF-1 is associated with cancer progression. It was a poor prognostic factor in breast cancer, clear cell renal carcinoma, gastric, prostate, endometrial, and bladder cancer [ 42 , 47 , 50 , 52 ]. In vitro studies revealed that NUCB2/NESF-1 increases invasion, migration, and proliferation in the colon, bladder, papillary thyroid, endometrial, renal, breast cancer cells, and glioblastoma [ 41 , 46 , 50 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, a high expression of nucleobindin-2/NESF-1 is associated with poor outcomes in breast, colon, bladder, prostate, gastric, renal, and endometrial cancer [ 16 , 17 , 18 , 19 , 20 ]. It was demonstrated that NUCB2/NESF1 intensified proliferation, invasion, and migration processes in colon, breast, endometrial, papillary thyroid, bladder, and renal cancer cells [ 19 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%